Near full-length HIV type 1M genomic sequences from Cameroon: Evidence of early diverging under-sampled lineages in the country - Tongo, Marcel (Evol Med Public Health, 2015)
Background: Cameroon is the country in which HIV-1 group M (HIV-1M) likely originated and is today a major hotspot of HIV-1M genetic diversity. It remains unclear, however, whether the highly divergent HIV-1M lineages found in this country arose during the earliest phases of the global HIV-1M epidemic, or whether they arose more recently as a result of recombination events between globally circulating HIV-1M lineages. Methodology: To differentiate between these two possibilities, we performed phylogenetic analyses of the near full genome sequences of nine newly sequenced divergent HIV-1M isolates and 15 previously identified, apparently unique recombinant forms (URFs) from Cameroon. Results: Although two of the new genome sequences were clearly classifiable within subtype G, the remaining seven were highly divergent and phylogenetically branched either outside of, or very near the bases of clades containing the well characterised globally circulating viral lineages that they were most closely related to. Recombination analyses further revealed that these divergent viruses were likely complex URFs. We show, however that substantial portions (>1 Kb) of three of the new genome sequences and 15 of the previously characterised Cameroonian URFs have apparently been derived from divergent parental viruses that branch phylogenetically near the bases of the major HIV-1M clades. Conclusions and implications: Our analyses indicate the presence in Cameroon of contemporary descendants of numerous early-diverging HIV-1M lineages. Further efforts to sample and sequence viruses from such lineages could be crucial both for retracing the earliest evolutionary steps during the emergence of HIV-1M in humans, and accurately reconstructing the ancestral sequences of the major globally circulating HIV-1M lineages.